Isolation, purification and preliminary structural determination of the toxins from scorpion Lychas mucronatus - Anh, Hoang Ngoc; Hoang, Dang Tran; Hai, Truong Nam; A., Fournier (Academia Journal of Biology, 2014)
Our study has showed that the scorpion species H. petersii petersii was abundant in the Dacnong province, but the scorpion one L. mucronatus many distributed in the Tayninh, Binhphuoc and Baria-Vungtau provinces. Five neurotoxins were isolated, purified and identified from the venom of L. mucronatus by using the RP-HPLC on C18 column and Mass-Spectrum. These isolated toxins had molecular masses as: 4326 Da, 4060 Da, 4914 Da, 4138 Da and 3965 Da respectively, that were similar to the molecular masses of the known toxins 5, 7, 9, 13 and 19 [6]. The structural determination of these toxins showed that in their molecules, there were three disulfide bridges what were typical for the short scorpion neurotoxins.